2022
DOI: 10.1088/1755-1315/974/1/012029
|View full text |Cite
|
Sign up to set email alerts
|

Water use efficiency of sugarcane clones under rainfed condition

Abstract: Crop water use study is necessary for crop management. The purpose of the research was to determine water use efficiency (WUE) of sugarcane clones under rainfed conditions. A field trial was carried out in rainfed at Kediri, East Java, from August 2018 to June 2020 in two seasons of plant cane (PC) and first ratoon cane (RC1). A Split-Plot Design was used for the field trial with three replications. Three planting arrangements were allocated to the main plot. Sub-plots consisted of five clones and one check va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…The average water demand of sugarcane plants ranges from 20 ML/ha, and approximately 80% of the total needs are met from groundwater [1]. Riajaya and Kadarwati [16] found that sugarcane plants have a peak water demand of 63.19% during the mid-season phase (grand growth or maximum development of sugarcane plant) of total evapotranspiration. Evaporation during the grand growth period greatly determines sugarcane yield and accounts for >68% of yield variation in South Africa [17].…”
Section: Introductionmentioning
confidence: 99%
“…The average water demand of sugarcane plants ranges from 20 ML/ha, and approximately 80% of the total needs are met from groundwater [1]. Riajaya and Kadarwati [16] found that sugarcane plants have a peak water demand of 63.19% during the mid-season phase (grand growth or maximum development of sugarcane plant) of total evapotranspiration. Evaporation during the grand growth period greatly determines sugarcane yield and accounts for >68% of yield variation in South Africa [17].…”
Section: Introductionmentioning
confidence: 99%